Implementation of a firebed cooling device and its influence on emissions and combustion parameters at a residential wood pellet boiler. (1st December 2015) - Gehrig, M.; Pelz, S.; Jaeger, D.; Hofmeister, G.; Groll, A.; Thorwarth, H.; Haslinger, W.
Highlights: A water-based firebed cooling was implemented into a residential wood pellet boiler. Influence of firebed temperature on gaseous and particle emissions was investigated. The combustion process is not impaired by reduced firebed temperatures. Reduced firebed temperatures lead to decreased particle emissions. Abstract: This study investigates the general concept of reduced firebed temperatures in residential wood pellet boilers. Residential wood pellet boiler development is more and more concerned with inorganic aerosols characterized by a temperature-dependent release from the firebed. Hence, different concepts are applied aiming to reduce firebed temperatures. Unfortunately, these concepts influence not only firebed temperatures, but also other important parameters like air flow rates which may cause unwanted side effects with respect to combustion quality or efficiency. Thus, a new approach was developed solely affecting firebed temperature by implementing a water-based firebed cooling in a 12 kW underfeed pellet boiler. The effectiveness of the cooling was monitored by comprehensive temperature measurement in the firebed. The cooling capacity ranged from 0.4 kW to 0.5 kW resulted in a significant decrease of firebed temperatures. Gaseous emissions remain stable showing no significant changes in major components (O2, CO2, NO x ). Furthermore, CO emissions were even reduced significantly by the activated cooling, which was supposedly caused by a stabilized devolatilization due to the firebed cooling. Moreover, the temperature-dependent release of aerosol forming elements was influenced at activated firebed cooling, which is proved by a decrease of 17 wt% of dust (Total Suspended Particles; TSP). At the same time the gaseous emissions of HCl increase, supposedly by a reduced potassium release from the firebed to the gas phase and a subsequently different particle formation. The general concept of reduced firebed temperatures proved to be successful decreasing overall aerosol emissions without impacting combustion quality.